Assessment of accessible, clean and efficient energy systems: A statistical analysis of composite energy performance indices. (15th December 2021) - Sandu, Suwin; Yang, Muyi; Phoumin, Han; Aghdam, Reza Fathollahzadeh; Shi, Xunpeng
Abstract: Motivated by a lack of a fuller understanding of the likely impact of energy policies on achieving overall positive outcomes of the energy systems, this paper aims to assess the performance of energy systems from three dimensions, i.e., availability, acceptability, and efficiency. Using a sample of 129 economies (grouped into three – advanced, emerging, and potential) over the period 1990–2016, we find that the overall performance of the energy systems has improved across the economies, with the most improvement in the advanced economies where the improvement occurred in all dimensions, particularly the acceptability dimension. In contrast, the main source of improvement in less-advanced (emerging and potential) economies was energy availability, but such an improvement was partially offset by the deteriorated acceptability dimension. These findings imply that such a varied outcome on energy performance is the result of unbalanced policy approaches in less-advanced economies that may have been implemented without a clear understanding of a potentially-unintended consequence of policy measures, and, if continued, may undermine the overall improvement of their future energy systems. Such an insight is arguably useful for policymakers to develop a much more balanced approach for developing energy systems.